MENINGKATKAN KEMAMPUAN MENGENAL HURUF MELALUI PERMAINAN MENCARI HURUF YANG HILANG DI TK WAHIDIN KELOMPOK B2 BAGANSIAPIAPI KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Darmawati Darmawati; Zulkifli N Zulkifli N; Nurlita Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of this study is most children are less familiar with the letters a through z. There are some children can name and recognize letters but irregular. In the child's name and recognize letters are often reversed, as well as in writing letters. Class actions performed in 2 cycles. Data collection tool used in this study is a sheet of observation. The number of samples in this study were 20 children consisting of 7 boys and 13 girls. The ability of children recognize letters starting from prasiklus that the average value of 40.00%. Direkapitulasikan ability to recognize letters after children in the first cycle obtained an average value of 51.33%. So the researchers went kesiklus II. Direkapitulasikan ability to recognize letters after children in the second cycle values obtained an average of 72.50%. Based on the analysis of the assessment process there was an increase of 2 cycles. Namely the increase that occurred before the action kesiklus I is 28.33%, Cycle I kesiklus II by 41.24%, and increased from the prior cycle to cycle II of 81.25%. From the results of these studies concluded that through the search for the missing letters game can improve children's ability to recognize letters B2 group Bagansiapiapi District of Bangko Rokan Hilir.Keywords: Recognize letters look for the missing letters